Comparison of a simplified skin pointer device compared with a skeletal marker for knee rotation laxity: A cadaveric study using a rotation-meter - Puah, Ken Lee (World J Orthop, 2018)
AIM: To compare the measurements of knee rotation laxity by non-invasive skin pointer with a knee rotation jig in cadaveric knees against a skeletally mounted marker. METHODS: Six pairs of cadaveric legs were mounted on a knee rotation jig. One Kirscher wire was driven into the tibial tubercle as a bone marker and a skin pointer was attached. Rotational forces of 3, 6 and 9 nm applied at 0°, 30°, 45°, 60° and 90° of knee flexion were analysed using the Pearson correlation coefficient and paired t-test. RESULTS: Total rotation recorded with the skin pointer significantly correlated with the bone marker at 3 nm at 0° (skin pointer 23.9 ± 26.0° vs bone marker 16.3 ± 17.3°, r = 0.92; P = 0.0), 30° (41.7 ± 15.5° vs 33.1 ± 14.7°, r = 0.63; P = 0.037), 45° (49.0 ± 17.0° vs 40.3 ± 11.2°, r = 0.81; P = 0.002), 60° (45.7 ± 17.5° vs 34.7 ± 9.5°, r = 0.86; P = 0.001) and 90° (29.2 ± 10.9° vs 21.2 ± 6.8°, r = 0.69; P = 0.019) of knee flexion and 6 nm at 0° (51.1 ± 37.7° vs 38.6 ± 30.1°, r = 0.90; P = 0.0), 30° (64.6 ± 21.6° vs 54.3 ± 15.1°, r = 0.73; P = 0.011), 45° (67.7 ± 20.6° vs 55.5 ± 9.5°, r = 0.65; P = 0.029), 60° (62.9 ± 22.4° vs 45.8 ± 13.1°, r = 0.65; P = 0.031) and 90° (43.6 ± 17.6° vs 31.0 ± 6.3°, r = 0.62; P = 0.043) of knee flexion and at 9 nm at 0° (69.7 ± 40.0° vs 55.6 ± 30.6°, r = 0.86; P = 0.001) and 60° (74.5 ± 27.6° vs 57.1 ± 11.5°, r = 0.77; P = 0.006). No statistically significant correlation with 9 nm at 30° (79.2 ± 25.1° vs 66.9 ± 15.4°, r = 0.59; P = 0.055), 45° (80.7 ± 24.7° vs 65.5 ± 11.2°, r = 0.51; P = 0.11) and 90° (54.7 ± 21.1° vs 39.4 ± 8.2°, r = 0.55; P = 0.079). We recognize that 9 nm of torque may be not tolerated in vivo due to pain. Knee rotation was at its maximum at 45° of knee flexion and increased with increasing torque. CONCLUSION: The skin pointer and knee rotation jig can be a reliable and simple means of quantifying knee rotational laxity with future clinical application.